The time-dependent yield of invasive vs. standard resuscitation strategies: A secondary analysis of the Prague out-of-hospital cardiac arrest study - Grunau, Brian; Rob, Daniel; Huptych, Michal; Pudil, Jan; Havránek, Štěpán; Kaválková, Petra; Šmalcová, Jana; Bělohlávek, Jan (Resuscitation, 2024)
BACKGROUND: It is unclear how invasive resuscitative protocols may impact the time-dependent prognosis of out-of-hospital cardiac arrest (OHCA) resuscitations, or the relationship between intra-arrest transport and outcomes. METHODS: We performed a secondary analysis of the Prague OHCA Study, which randomized refractory OHCAs to "invasive" (intra-arrest transport for possible ECPR initiation) vs. "standard" resuscitation strategies (predominantly performed on-scene). Between groups, we compared outcomes of the initial resuscitation and 180- and 30-day favourable neurological outcomes (CPC 1-2), and within categories based on resuscitation duration (collapse-to-ROSC/ECPR interval). We plotted the dynamic probability of favourable outcomes with increasing durations of unsuccessful resuscitation. RESULTS: Among invasive and standard groups, respectively: 34/124 (27%) vs. 58/132 (44%) had sustained ROSC (difference -17%, 95%CI -5.0, -28); 38/124 (31%) vs. 24/132 (18%) had 30-day favourable neurological outcomes (difference 12%; 95%CI 2.0, 23); and 39/124 (31%) vs. 29/132 (22%) had 180-day favourable neurological outcomes (difference 9.5%; 95%CI -1.3, 20). For favourable outcome cases: standard group resuscitation durations were right-skewed within the first 60 min; for the invasive group the distribution was bimodal, extending to 77 min. For invasive- and standard-treated cases, the probability of favourable outcomes among those in refractory arrest at 30 min was 28% and 7.6%, respectively; declining to 0% at 77 and 60 min. CONCLUSION: In comparison to standard resuscitation, invasive strategy cases had fewer achieve sustained ROSC, however improved overall 30-day favourable neurological outcomes. While standard resuscitation yield was limited to < 60 min, invasive protocols offer a second extended window of potential successful resuscitation.
Keywords: časové faktory; urgentní zdravotnické služby; kardiopulmonální resuscitace; Time Factors; Out-of-Hospital Cardiac Arrest; Male; Aged; lidé; Female; mužské pohlaví; ženské pohlaví; senioři; lidé středního věku; Cardiopulmonary Resuscitation; Humans; Emergency Medical Services; zástava srdce mimo nemocnici; Middle Aged